The Improvement in Poetry Writing Skills by Using Prezi in the Primary School - Susanti, Atika; Mustadi, Ali; Asnimar, Asnimar; Susiloningsih, Esti (Universitas Pendidikan Indonesia, 2019)
Writing is one of the subjects taught at school. Through poetry writing, students’ imaginative writing skills can be improved. The purpose of this research is to describe the improvement in poetry writing skills and students’ activity using Prezi. This research employed a classroom action research method conducted in three cycles. Each cycle consisted of four stages, namely: planning, implementation, observation, and reflection. The subjects of this research were fifth-grade students of a primary school in Inderalaya consisting of 13 male students and 16 female students. The instrument of the data collection was a poetry writing test. The results of the three cycles in this research were 44.44%, 78.57%, and 89.28% respectively. It showed an increase in poetry writing skills of fifth-grade primary school students after the use of Prezi media in learning. Hence, it can be concluded that Prezi was an appropriate media to teach poetry writing. It is recommended that Prezi could be used as an alternative media to teach writing in the primary school.